Effect of alloying on ductility and low cycle fatigue behaviour of Ti, Ni and Fe based aluminides - Praveen K.V.U.; Singh V. (My University, 2025)
Aluminides of Ti, Ni and Fe are ordered intermetallics and possess many attractive properties for high temperature application. Aluminides with high Al content like TiAl, NiAl and FeAl have relatively lower density, better oxidation resistance and superior mechanical properties than their counterparts with lower Al content (Ti3Al, Ni3Al and Fe3Al). However, in general, aluminides display poor ductility at ambient temperature and even upto their order/disorder transformation temperature. Various attempts have been made to improve ductility of both M3A1 and MAI type aluminides through different routes. As compared to tensile and creep properties, less attention has been paid on the LCF behavior of these aluminides particularly of Ni and Fe based ones. LCF behavior of different types of aluminides is discussed.